Intelligent control of an autonomous unmanned aerial vehicle - Tan, Benjamin Hao Yang (2015)
In the earlier days, Unmanned Aerial Vehicle (UAV) had been invented to be used for military applications like bombing and reconnaissance. In the recent years, there has been an increasing popularity for Quadcopters, a type of Vertical Take Off and Landing (VTOL) UAV. The Quadcopter has been developed and is currently used for many military, civil and commercial applications. It has also become a hobby for many remote controlled aircraft enthusiast. In this project, the Quadcopter had been built from scratch and a microcontroller had been integrated with the on board flight controller so that the microcontroller can control the flight of the Quadcopter. Many components like the Servo Motor, Sensor and Xbee had been integrated with the microcontroller to increase the number of tasks which the Quadcopter is able to perform. Sensors like the ultrasonic sensor was then integrated with the microcontroller so as to detect the various parameters of the Quadcopter. These data obtained is then used to model and develop algorithm to control the Quadcopter. An algorithm to perform altitude hold had been developed and implemented on this Quadcopter. Together with other implemented features, the Quadcopter had been showcased during the Singapore Amazing Flying Machine Competition 2015 and its capability to navigate through the obstacle course while perform missions within the course was demonstrated.